2007
DOI: 10.1002/j.2161-0045.2007.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Specialty Preferences Among Psychology Majors: Cognitive Processing Styles Associated With Scientist and Practitioner Interests

Abstract: The authors investigated cognitive processing styles associated with interests in scientist and practitioner activities among a sample of undergraduate psychology majors who planned to attend graduate school. Results indicated that interests in scientist activities were associated with a greater motivation to engage in effortful processing (i.e., need for cognition). Interests in practitioner activities were not correlated with need for cognition. Contrary to theoretical expectations, neither interests in scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…Students at Social Psychology show relatively more interest in foreign languages and cultural topics. The picture emerging from group differences in personality and cognitive abilities is consistent with previous findings in the US (Bishop & Bieschke, 1998;Horn et al, 2007;Leong et al, 2007;Mallinckrodt et al, 1990;Martin et al, 2007;Tinsley et al, 1993;Vittengl et al, 2004). The different specialties of psychology can best be characterized in terms of different Holland codes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Students at Social Psychology show relatively more interest in foreign languages and cultural topics. The picture emerging from group differences in personality and cognitive abilities is consistent with previous findings in the US (Bishop & Bieschke, 1998;Horn et al, 2007;Leong et al, 2007;Mallinckrodt et al, 1990;Martin et al, 2007;Tinsley et al, 1993;Vittengl et al, 2004). The different specialties of psychology can best be characterized in terms of different Holland codes.…”
Section: Discussionsupporting
confidence: 77%
“…Research among psychology majors in the US has highlighted a clear distinction between researcher and practitioner interests (Leong & Zachar, 1991;Zachar & Leong, 1992. Several studies have addressed the relatively low interest in scientific issues among many psychology majors (Bishop & Bieschke, 1998;Leong, Zachar, Conant, & Tolliver, 2007;Tinsley, Tinsley, Boone, & Shim Li, 1993;Vittengl et al, 2004), although psychology majors clearly differ in this regard. For instance, Martin, Gavin, Baker, and Bridgmon (2007) recently compared doctoral students at different specialties of psychology and found clear differences between these groups in scientist-practitioner interests.…”
Section: Introductionmentioning
confidence: 98%
“…We hope that the initial development of the present questionnaire will lead to further international and, perhaps, crosscultural studies. It is essential that universities offer guidance through the use of questionnaires/scales that are appropriate for their students' needs (Leong et al, 2007). Furthermore, it is essential to identify and overcome the difficulties that vocational and professional psychology students present during their course.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing psychology students with students from other courses, a study developed by Leong, Zachar, Conant, & Tolliver (2007) showed that psychology students were more active and enthusiastic entrepreneurs than geography students (higher openness scores) and more inhibited than physical education students (lower extraversion scores). Other authors argued that different forms of cognition that characterize psychology students, namely creativity, appear to be directly linked to innovation and the search for new solutions (e.g., Cassin et al, 2007;Jones & Allen, 2012;Wicherts & Vorst, 2010).…”
Section: Interests In Career Areas Of Psychologymentioning
confidence: 98%
See 1 more Smart Citation